Architectural Elements in Islamic Content and their Influence on Modern Architectural Spaces in Jordan Case Study: "Using the Fountain in Buildings (Residential and Public) and Gardens": العناصر المعمارية المائية في المضمون الإسلامي وطرق تأثيرها على الفراغات المعمارية المعاصرة في الأردن حالة دراسية: "استخدام النافورة في المباني (السكنية والعامة) والحدائق" - Mona Issa Saleh Al - Sukkar, (Journal of engineering sciences and information technology, 2017)
The Islamic architecture has a clear impact on contemporary Jordanian architecture and on the work of some Jordanians architects, where some of them deliberately tried to simulate a range of vocabularies and visual concepts that have symbolic and environmental functions lend its own character on the architectural output and take into account the climatic and socio-economic conditions, the research aims to study the effects of Islamic architecture in a contemporary architectural spaces with regard to water architectural features by measuring the degree of vulnerability to the fountain element and employment of this element in several buildings including residential and public as well as in the gardens, where the fountain has links to symbolic and semantic as well as environmental functions, therefore the research reviews on this will address some views in addition to analyses and study the uses of this element in the traditional architectural facilities through the theoretical approach based on the analysis of scientific literature in addition to the analytical approach to study a set of study cases and contemporary buildings that contained in its formation of this element, And compare these analyzes and studies together to arrive at conclusions that emphasize the roles of water elements and the success of contemporary Jordanian architects by employing the water element to re-establish Islamic values in contemporary architecture.